The Role and Strategy of Village-Owned Enterprises in Conducting Economic Empowerment of Village Communities - Denis Ayu Fitriani; Slamet Santoso; Choirul Hamidah (Budapest International Research and Critics University, 2022)
Based on Law No. 6 of 2014, the establishment of village-owned enterprises (BUMDes) aims to encourage and accommodate all activities to increase community income man. The role of BUMDes is to become a pillar of community independence in accommodating community economic activities to improve community welfare, so this research uses a qualitative descriptive type of research. It is said to be qualitative because the main data source in this research is the words and actions of the people who are observed or interviewed. While it is descriptive, that is, the researcher describes an object, phenomenon, which will be written in narrative writing. In terms of place, this research is a type of field research with the hope that BUMDes will be able to create a more efficient society.